Synthesis, intramolecular cyclization and anti-inflammatory activity of substituted 2-(2-(Furan-2-carbonyl)hydrazono)-4-oxobutanoic Acids - Sergei N. Igidov; Dmitriy V. Lipin; Aleksey Yu. Turyshev; Svetlana V. Chashchina; Daria A. Shipilovskikh; Ol’ga V. Zvereva; Ksenia A. Mitusova; Pavel S. Silaichev; Nazim M. Igidov (Chimica Techno Acta)
A method was proposed for the synthesis of substituted 2-(2-(furan-2-carbonyl)hydrazono)-4-oxobutanoic acids by the reaction of substituted 2,4-dioxobut-2-enoic acids with furan-2-carbohydrazide. It was found that substituted 2-(2-(furan-2-carbonyl)hydrazono)-4-oxobutanoic acids undergo intramolecular cyclization in the presence of propionic anhydride to form the corresponding N'-(2-oxofuran-3(2H)-ylidene)furan-2-carbohydrazides. The anti-inflammatory activity of the obtained compounds was studied. It was found that the obtained compounds have pronounced anti-inflammatory activity.